2011
DOI: 10.2169/internalmedicine.50.4476
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metabolic Syndrome and Carotid Atherosclerosis: Relevance of Combined Criteria Including the Serum Adiponectin Level for the General Population

Abstract: Objective The association between carotid atherosclerosis and the metabolic syndrome (MetS) was analyzed in the general population. The usefulness of the inclusion of the serum adiponectin concentration in the MetS criteria for the detection of atherosclerosis was also examined. Patients and MethodsThe 825 participants of a comprehensive health checkup who underwent carotid ultrasonography and the measurement of serum adiponectin levels were studied. Results The carotid plaque score (PLS) was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, it remains unclear whether the predictive role of adiponectin levels is dependent on gender. A recent study in Japan 19 showed that the applicability of diagnostic criteria for MetS in adult males was inferior to the criteria for females. This study also found that replacing WC with the adiponectin level in the diagnostic criteria for MetS may be useful for identifying more males with CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether the predictive role of adiponectin levels is dependent on gender. A recent study in Japan 19 showed that the applicability of diagnostic criteria for MetS in adult males was inferior to the criteria for females. This study also found that replacing WC with the adiponectin level in the diagnostic criteria for MetS may be useful for identifying more males with CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines, such as adiponectin, are secreted by the adipose tissue or as a result of glucose and lipid metabolism. [2022]. Accordingly, the level of adiponectin is associated with obesity-related disorders and metabolic risk factors [2326].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between MetS and the localization of arteriosclerosis remains uncertain. In subjects with MetS, carotid atherosclerosis on ultrasonography has been identified in several investigations (21)(22)(23)(24). Several authors (25)(26)(27) have found that asymptomatic cerebral infarction on MRI is significantly more frequently detected in subjects with MetS.…”
Section: Discussionmentioning
confidence: 99%